2021
DOI: 10.3390/nu13030980
|View full text |Cite
|
Sign up to set email alerts
|

Fruit and Vegetable Intake Assessed by Repeat 24 h Recalls, but Not by A Dietary Screener, Is Associated with Skin Carotenoid Measurements in Children

Abstract: Accurate measurement of fruit and vegetable (FV) intake is important for nutrition surveillance and evaluation of dietary interventions. We compared two tools for reporting FV intake to objective measurement of skin carotenoids among children. FV cups/day was assessed by repeated 24 h dietary recalls (24H FV) and the National Cancer Institute’s All-Day Fruit and Vegetable Screener (NCI FV). Skin carotenoids were measured by repeated resonance Raman spectroscopy (RRS) of the palm. FV cups were regressed on RRS … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…Such information is currently available for RRS but not RS. For example, for RRS, one study demonstrates that 30,489.8 (±4667.1) RRS units of SCS in children translates into 0.5 cups of FV/day consumption [ 35 ]. Therefore, future randomized control trials are recommended to establish reference points for using RS-based SCS to estimate children’s daily FVC, similar to RRS.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Such information is currently available for RRS but not RS. For example, for RRS, one study demonstrates that 30,489.8 (±4667.1) RRS units of SCS in children translates into 0.5 cups of FV/day consumption [ 35 ]. Therefore, future randomized control trials are recommended to establish reference points for using RS-based SCS to estimate children’s daily FVC, similar to RRS.…”
Section: Discussionmentioning
confidence: 99%
“…A newer and advanced alternative method to RRS for SC assessment includes pressure-mediated reflection spectroscopy (RS) [ 32 , 33 , 34 ]. RS has been validated with plasma carotenoid status in adults [ 32 , 34 , 35 , 36 ] but not in children. RS uses a broader band of LED light from 350 to 850 nm of the spectral range [ 33 ].…”
Section: Introductionmentioning
confidence: 99%
“…Total FVI included legumes, 100% fruit juice, and fried potatoes [ 31 ]. This method has been validated for use in studies with limited data [ 32 ] to evaluate child FVI [ [33] , [34] , [35] ].…”
Section: Methodsmentioning
confidence: 99%
“…Correspondingly, they were compared with FV consumptions, which were assessed by various tools, for example, 24 h recalls, fruit and vegetable intake frequency questionnaire, food frequency screener, and liking survey. Skin carotenoids measured by RRS were positively associated (r > 0.35, p < 0.05) with total FV consumption [24][25][26][27][28], except in a study in which FV intake was assessed by the National Cancer Institute's All-Day Fruit and Vegetable (NCI FV) Screener [26]. In this study, the authors used two tools to assess FV intake-NCI FV and 24 h dietary recall (24H FV)-and they suggested that the NCI FV screener is not a valid tool for FV intake assessment [26].…”
Section: Skin Biomarkersmentioning
confidence: 99%
“…Skin carotenoids measured by RRS were positively associated (r > 0.35, p < 0.05) with total FV consumption [24][25][26][27][28], except in a study in which FV intake was assessed by the National Cancer Institute's All-Day Fruit and Vegetable (NCI FV) Screener [26]. In this study, the authors used two tools to assess FV intake-NCI FV and 24 h dietary recall (24H FV)-and they suggested that the NCI FV screener is not a valid tool for FV intake assessment [26]. RRS scores were also verified by serum and plasma carotenoid concentrations separately in two studies [24,27], in which blood carotenoids were measured by high-performance liquid chromatography.…”
Section: Skin Biomarkersmentioning
confidence: 99%